"It's really no more difficult than putting on fluoride varnish": a qualitative exploration of dental professionals' views of silver diamine fluoride for the management of carious lesions in children - Nassar Seifo; Heather Cassie; John Radford; Nicola Innes (BMC, 2020)
Abstract Background Despite evidence that Silver Diamine Fluoride (SDF) can be effective in managing carious lesions in primary teeth, the use of SDF in the UK remains limited. This study explored dental professionals' views and experiences of using SDF for managing carious lesions in children. In addition, it explored what they perceived to be the advantages, disadvantages, barriers and enablers to the use of SDF in practice. Methods Fifteen semi-structured face-to-face or over-the-phone interviews were conducted with 14 dental professionals from NHS Tayside and NHS Grampian in Scotland. Interviews were transcribed verbatim, coded and analysed using a thematic approach. Results Thirteen of 14 dental professionals interviewed were familiar with, or had some existing knowledge of, SDF. Four had used it to treat patients. The majority of participants thought that the main advantage of SDF was that it required minimal patient cooperation. SDF was also perceived as a simple, pain-free and non-invasive treatment approach that could help acclimatise children to the dental environment. However, SDF-induced black staining of arrested carious lesions was most commonly reported as the main disadvantage and greatest barrier to using it in practice. Participants believed that this discolouration would concern some parents who may fear that the black appearance may instigate bullying at school and that others may judge parents as neglecting their child's oral health. Participants thought that education of clinicians about SDF use and information sheets for parents would enhance the uptake of SDF in dental practice. Participants believed that younger children might not be as bothered by the discolouration as older ones and they anticipated greater acceptance of SDF for posterior primary teeth by both parents and children. Conclusion Dental professionals were aware that SDF can be used for arresting carious lesions. They pointed out that the staining effect of carious lesions is a major disadvantage and had preconceived ideas that this could be a barrier for many parents. Participants considered the application process to be simple and non-invasive and requires a minimum level of child cooperation. Participants appreciated the potential of SDF in paediatric dentistry and suggested actions that could help overcome the barriers they highlighted.